Detecting and predicting neutralization of alemtuzumab responses in MS. Issue 4 (July 2020) - Saxena, Gauri; Moore, James M.; Jones, Meleri; Pryce, Gareth; Ali, Liaqat; Leisegang, Georgia R.; Vijay, Vivek; Loveless, Samantha; Robertson, Neil P.; Schmierer, Klaus; Giovannoni, Gavin; Gnananpavan, Sharmilee; et al.
Abstract : Objective: To test the hypothesis that antidrug antibodies (ADAs) against alemtuzumab could become relevant after repeated treatments for some individuals, possibly explaining occasional treatment resistance. Methods: Recombinant alemtuzumab single-chain variable fragment antibody with a dual tandem nanoluciferase reporter linker was made and used to detect binding ADAs. Alemtuzumab immunoglobulin G Alexa Fluor 488 conjugate was used in a competitive binding cell-based assay to detect neutralizing ADAs. The assays were used to retrospectively screen, blinded, banked serum samples from people with MS (n = 32) who had received 3 or more cycles of alemtuzumab. Lymphocyte depletion was measured between baseline and about 1 month postinfusion. Results: The number of individuals showing limited depletion of lymphocytes increased with the number of treatment cycles. Lack of depletion was also a poor prognostic feature for future disease activity. ADA responses were detected in 29/32 (90.6%) individuals. Neutralizing antibodies occurred before the development of limited depletion in 6/7 individuals (18.8% of the whole sample). Preinfusion, ADA levels predicted limited, postinfusion lymphocyte depletion. Conclusions: Although ADAs to alemtuzumab have been portrayed as being of no clinical significance, alemtuzumab-specific antibodies appear to be clinically relevant for some individuals, although causation remains to be established. Monitoring of lymphocyte depletion and the antidrug response may be of practical value in patients requiring additional cycles of alemtuzumab. ADA detection may help to inform on retreatment or switching to another treatment.